Digital implementation of deadbeat-direct torque and flux control for permanent magnet synchronous machines in the M–T reference frame - Zuo, Yuefei (2020)
In the traditional deadbeat-direct torque and flux control in the M-T reference frame (DB-DTFC-MT) scheme, the stator flux is calculated with the current model, and one-step delay in the digital system is neglected, which results in poor robustness to parameter variations and a serious oscillation in both the stator flux and torque, especially in the low-speed range. In this paper, the digital implementation of DB-DTFC-MT is studied. Firstly, the DB-DTFC-MT scheme considering the one-step delay in the digital system is deduced. Secondly, digital stator flux observer and current observer are developed to predict the stator flux and current in the next sampling instant. By using the predicted stator flux and torque, the oscillation caused by the one-step delay is eliminated and real deadbeat control is realized. Moreover, the robustness of the system to parameter variations is qualitatively evaluated. Though the system shows some sensitivity to the permanent magnet flux, it has strong robustness to the stator resistance and inductances, especially the d-axis inductance. Hence, a larger estimated d-axis inductance can be used in the system for reducing the pulsation in the d-axis current when tracking sinusoidal torque. All the proposed control designs are validated on a real-time control platform based on dSPACE DS1103.